Emotional and cognitive behavioural therapies on academic performance of secondary school students with attention deficit hyperactivity disorder in Ibadan, Oyo State, Nigeria (2021)
The study determined the effectiveness of emotional and cognitive behavioural therapies in enhancing the academic performance of ADHD in Mathematics among senior secondary school students in Ibadan. To ascertain the degree of therapeutic efficacy, a randomized sample of 45 senior secondary school students with 15 participants in each from three different senior special schools in three different local government areas in Ibadan were chosen for the purpose. The quasi-experimental study employed a randomized sample that undertook training in Emotional and Cognitive Behavioural Therapies and with a control group were used. The instrument used for data collection are Mathematics achievement tests prepared by the National Examination Council (NECO) for 2017 & 2018 objective Mathematics papers were used since the instrument was prepared by the Public Examination body there is no need for revalidation of the instrument. A pair of pre-test and post-test data was obtained from each participant who formed the basis of the findings using ANCOVA for data analyses. Three hypotheses were formulated and tested at α = 0.05 level of significance. Results showed that there were significant differences in the treatment with Cognitive Behavioural Therapy being more significant in enhancing Mathematics achievement among ADHD senior school students. Also, the results showed that gender and age have to do with the enhancement of academic performance among senior secondary school students with ADHD. It was therefore concluded that Emotional and Cognitive Behavioural Therapies can be used to enhance senior Mathematics academic performance of students with ADHD and recommendations are also offered.